Caracterização da silagem do sorgo forrageiro AGRI 002E e utilização na alimentação de bovinos - Venturini, Tiago (2019)
This work aimed to evaluate the effect of the use of additives on the fermentation profile and on the quality of forage sorghum silage and its use in feeding dairy cattle to corn silage. Nutritional evaluation of forage sorghum silage in natura, and after silage (28 and 56 days) with addition of bacterial inoculant and urea were performed. The fermentation profile, losses and microbial populations of forage sorghum silage with inclusion of bacterial inoculant and urea were determined along the fermentation process (0, 1, 3, 7, 14, 28 and 56 days of opening). The contents of DM, OM, total carbohydrates, NFC, IVDDM, IVDOM and organic acid concentrations increased with ensiling times. On the other hand, there was a reduction in the concentrations of condensed tannins, NDF, cellulose, ADF and WSC. The urea contributed to increase CP and IVDCP contents and reduction in NDF, hemicellulose and NFC concentrations in relation to the bacterial inoculant and control silages. The addition of urea to sorghum silage contributes to the improvement of the nutritive value of the material. The bacterial inoculant does not alter the fermentative quality of the silage under the conditions tested. Silages with 28 days of silage are stable and ready for use. The DM recovery, EL and GL increased during the opening days; in addition, the DM recovery was smaller with the inclusion of urea. The pH and temperature were reduced and stabilized after ensiling, and the pH increased in urea treatments. The LAB increased the population according to the opening days, however, the population of enterobacteria and yeasts reduced. Clostridia reduced as a function of the additives with longer opening times. Seven genera of fungi were identified in the ensiled material and reduced throughout the fermentation process. In a study with cows, the objective was to evaluate the intake and digestibility of dry matter and nutrients as a function of the replacement (0%, 25%, 50%, 75% and 100%) of corn silage by forage sorghum diet of lactating cows. Fodder sorghum silage reduces the intake and digestibility of DM and nutrients, but doesn’t alter milk production and composition, microbial synthesis and blood metabolites indicate absence of liver problems. Evaluating the digestibility and ruminal parameters in cattle due to the replacement of corn silage for sorghum silage doesn’t alter the digestibility of dry matter and nutrients and maintain the ruminal parameters under normal conditions.